HIV infection, hunger, breastfeeding self-efficacy, and depressive symptoms are associated with exclusive breastfeeding to six months among women in western Kenya: a longitudinal observational study - Emily L. Tuthill; Joshua D. Miller; Shalean M. Collins; Elizabeth M. Widen; Maricianah Onono; Sera L. Young (BMC, 2020)
Abstract Background Exclusive breastfeeding for the first six months of life is recommended for all infants. However, breastfeeding rates remain suboptimal; around 37% of infants are exclusively breastfed for the first six months globally. In Nyanza region, western Kenya, numerous challenges to breastfeeding have been identified, including food insecurity, hunger, depressive symptoms, and HIV infection. Yet, evidence to inform our understanding of how these problems influence women's breastfeeding behaviors across time is lacking. We therefore sought to examine these factors and how they interact to affect the initiation and duration of exclusive breastfeeding in this region. We hypothesized that women experiencing greater food insecurity, hunger, and/or depressive symptoms would be less likely to maintain exclusive breastfeeding for six months than women who were food secure or not depressed. We also hypothesized that women living with HIV would be more likely to maintain exclusive breastfeeding to six months compared to HIV-uninfected women. Methods Women in Pith Moromo, a longitudinal cohort study in western Kenya, were surveyed at two antenatal and three postpartum timepoints (n = 275). Data were collected on breastfeeding behavior and self-efficacy, maternal food insecurity and hunger, maternal psychosocial health, and HIV status. Cox proportional hazards models were used to identify predictors of early exclusive breastfeeding cessation. Results The majority of women (52.3%) exclusively breastfed for the first six months. In the final multivariable Cox proportional hazards model, living with HIV was associated with a 64% decrease in the rate of early exclusive breastfeeding cessation. Additionally, the rate of early exclusive breastfeeding cessation increased by 100 and 98% for those experiencing probable depression or hunger, respectively. Although there was no main effect of breastfeeding self-efficacy, the interaction between breastfeeding self-efficacy and hunger was significant, such that the rate of early exclusive breastfeeding cessation was predicted to decrease by 2% for every point increase in breastfeeding self-efficacy score (range: 0-56). Conclusions This study contributes to previous work demonstrating that women living with HIV more consistently exclusively breastfeed and suggests that rates of exclusive breastfeeding could be increased through targeted support that promotes maternal mental health and breastfeeding self-efficacy, while reducing maternal hunger. Trial registration Study registration NCT02974972.